Vulnerability profile of the elderly population in primary health care in Canoas-RS using the VES-13 - Mariana S. Forster; Maria E. S. Affonso; Marjana M. Wojcicki; Tricia N. M. Rosa; Maria R. Burg; Miria E. B. Camargo (International Journal Of Community Medicine And Public Health, 2026)
Background: Population aging has been accompanied by an increased prevalence of frailty and vulnerability among older adults, especially in more advanced age groups. This study aimed to assess the vulnerability of older adults residing in Canoas, RS, using the Vulnerable Elders Survey (VES-13), and to analyze its association with sociodemographic variables, self-rated health, and functional capacity. Methods: This was a cross-sectional study including a sample of 1,260 older adults seen at Primary Health Care Centers in Canoas, RS, during the post-pandemic period. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) and Pearson’s chi-square test. Results: Most participants were younger than 75 years (56.7%), and 67.8% were female. Individuals aged 85 years or older showed a progressive increase in negative self-rated health (67.6%; p=0.02), as well as in physical limitations and disabilities in activities of daily living (p=0.01). The mean VES-13 score increased from 2.01 among those younger than 75 years to 8.10 among the oldest-old (p